Association between time of day and CPR quality as measured by CPR hemodynamics during pediatric in-hospital CPR. (August 2020) - ,; Zuppa, Athena F.; Graham, Katherine; Twelves, Carolann; Diliberto, Mary Ann; Holubkov, Richard; Telford, Russell; Locandro, Christopher; Coleman, Whitney; Peterson, Alecia; Thelen, Julie; Heidemann, Sabrina; et al.
Abstract: Introduction: Patients who suffer in-hospital cardiac arrest (IHCA) are less likely to survive if the arrest occurs during nighttime versus daytime. Diastolic blood pressure (DBP) as a measure of chest compression quality was associated with survival from pediatric IHCA. We hypothesized that DBP during CPR for IHCA is lower during nighttime versus daytime. Methods: This is a secondary analysis of data collected from the Pediatric Intensive Care Quality of Cardiopulmonary Resuscitation Study. Pediatric or Pediatric Cardiac Intensive Care Unit patients who received chest compressions for ≥1 min and who had invasive arterial BP monitoring were enrolled. Nighttime was defined as 11:00PM to 6:59AM and daytime as 7:00AM until 10:59PM. Primary outcome was attainment of DBP ≥ 25 mmHg in infants <1 year and ≥30 mmHg in older children. Secondary outcomes were mean DBP, ROSC, and survival to hospital discharge. Univariable and multivariate analyses evaluated the relationships between time (nighttime vs. daytime) and outcomes. Results: Between July 1, 2013 and June 30, 2016, 164 arrests met all inclusion/exclusion criteria: 45(27%) occurred at nighttime and 119(73%) during daytime. Average DBPs achieved were not different between groups (DBP: nighttime 28.3 mmHg[25.3, 36.5] vs. daytime 29.6 mmHg[21.8, 38.0], p = 0.64). Relative risk of DBP threshold met during nighttime vs. daytime was 1.27, 95%CI [0.80, 1.98], p = 0.30. There was no significant nighttime vs. daytime difference in ROSC (28/45[62%] vs. 84/119[71%] p = 0.35) or survival to hospital discharge (16/45[36%] vs. 61/119[51%], p = 0.08). Conclusions: In this cohort of pediatric ICU patients with IHCA, there was no significant difference in DBP during CPR between nighttime and daytime.